Process analysis and risk management in a mineral water bottling company - Amorim, Matheus de Jesus; Silva, Jéssica Echer; Loyola, Vagner Viali; Xavier, Thiago Padovani (Brazilian Journal of Production Engineering, 2023)
Brazil is evolving in the bottling industry of mineral water, occupy occupying the position of one of the main water bottlers in the world. That said, this study proposes to discuss aspects related to the development of companies in the field and how they can improve their production process. This qualitative approach article verified the productive processes of a company and the risks to which the organization is exposed. Through process mapping and layout analysis, proposals for changes in the production area were elaborated to better store the final product and avoid possible rework related to packaging damage. In addition, based on the analysis of the risks associated with the organization and the use of the FMEA tool, suggestions for improvement were proposed for the company’s financial department.